Profile of Asphyxiated Babies at Tribhuvan University Teaching Hospital - Shrestha, M; Shrestha, L; Shrestha, PS (Journal of Nepal Paediatric Society, 2009)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–> <!–[if gte mso 10]> <![endif]–> Objective: To assess risk factors and outcome in the early neonatal period of babies who were asphyxiated at birth. Methodology: This was a retrospective study conducted at Tribhuvan University Teaching Hospital (TUTH) over a period of one year from 15th Feb 2007 to 14th Feb 2008. All the term babies who had Apgar score of less than < 6 at 1 minute of birth were included. Detailed maternal risk factors during pregnancy and labor were analyzed. The newborn babies who required admission in neonatal unit were again analyzed for development of hypoxic ischemic encephalopathy (HIE) and their outcome. Results: During the study period, out of 3594 term babies, 327 babies (9%) were asphyxiated. Of the total asphyxiated babies, 85% and 15% had moderate and severe asphyxia, respectively, at 1 minute of birth. Out of these asphyxiated babies, 51% and 7% had intrapartum and maternal risk factors, respectively. Intrapartum risk factors like meconium stained liquor, non-vertex presentation, and fetal heart rate abnormalities accounted for 4 fold risk of asphyxia. Of these babies, 26% required admission in nursery and 29% developed hypoxic ischemic encephalopathy. Among the admitted babies 6% expired, 2% left against medical advice and rest were discharged. Conclusion: Early identification and close monitoring of high risk mothers studies with maintaining partograph during labor will help to reduce neonatal asphyxia. Key words: Asphyxiated babies doi:10.3126/jnps.v29i1.1592 J. Nepal Paediatr. Soc. Vol.29(1) p.3-5